2016
DOI: 10.1186/s12940-015-0085-9
|View full text |Cite
|
Sign up to set email alerts
|

Misled about lead: an assessment of online public health education material from Australia’s lead mining and smelting towns

Abstract: BackgroundThis study assesses the accuracy and comprehensiveness of online public health education materials from the three Australian cities with active lead mines and or smelters: Broken Hill, Mount Isa and Port Pirie.MethodsQualitative content analysis of online Australian material with comparison to international best practice where possible.ResultsAll materials provided incomplete information about the health effects of lead and pathways of exposure compared to best practice materials. Inconsistent strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 21 publications
(21 reference statements)
5
59
1
Order By: Relevance
“…[25, 26, 28] Findings from these studies were consistent with observed associations in the present study. Findings from the present study showed a greater risk of neonatal, post-neonatal, child and under-five mortality when mothers reported no separate kitchen in the house and used polluting fuels for cooking, and also found increased risk of childhood mortality even where clean fuels were used but no separate kitchen in the house.…”
Section: Discussionsupporting
confidence: 92%
“…[25, 26, 28] Findings from these studies were consistent with observed associations in the present study. Findings from the present study showed a greater risk of neonatal, post-neonatal, child and under-five mortality when mothers reported no separate kitchen in the house and used polluting fuels for cooking, and also found increased risk of childhood mortality even where clean fuels were used but no separate kitchen in the house.…”
Section: Discussionsupporting
confidence: 92%
“…Risk factors that can affect exposure to pollution from soil and air include lifestyle factors and structural factors which are beyond the agency of residents. Attempts by governing bodies and the mines to address elevated BLLs have been aimed at changing personal behaviours that can increase exposure to lead (Forbes and Taylor 2015, Sullivan andGreen 2016). These have focused on the regular washing of hands and table surfaces in homes, growing lawns and regularly eating fresh fruit to reduce uptake of lead (Sullivan and Green 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, integrating epidemiological findings using analytic methods to more objectively identify sex-specific vulnerable early life windows with knowledge regarding brain and nervous system developmental pathways as well as hormonal and micronutrient milieu involved in perinatal programming of neuromotor functions that may be disrupted in these time periods as summarized in recent reviews (Golding et al, 2014; Pitcher et al, 2006; Sandman et al, 2011) may better inform future mechanistic research in this area. Of note, literature on other more widely studied neurodevelopmental domains, such as cognitive and behavioral outcomes, has also suggested sex differences in relation to early life Mn exposure, where stronger adverse associations seemed to be more likely to be found in girls, although some studies did not find evidence of effect modification by sex (Coetzee et al, 2016). …”
Section: Discussionmentioning
confidence: 99%